2019
DOI: 10.7150/thno.30309
|View full text |Cite
|
Sign up to set email alerts
|

The Applications of Radiomics in Precision Diagnosis and Treatment of Oncology: Opportunities and Challenges

Abstract: Medical imaging can assess the tumor and its environment in their entirety, which makes it suitable for monitoring the temporal and spatial characteristics of the tumor. Progress in computational methods, especially in artificial intelligence for medical image process and analysis, has converted these images into quantitative and minable data associated with clinical events in oncology management. This concept was first described as radiomics in 2012. Since then, computer scientists, radiologists, and oncologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
429
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 675 publications
(470 citation statements)
references
References 201 publications
(216 reference statements)
0
429
0
4
Order By: Relevance
“…Radiomics, an emerging approach for image interpretation, can non-invasively predict treatment response solely by radiographic examination (17). Radiomics can profile tumor heterogeneity of different responders by extracting extensively quantitative features that reflect underlying pathophysiology from medical images (18).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, an emerging approach for image interpretation, can non-invasively predict treatment response solely by radiographic examination (17). Radiomics can profile tumor heterogeneity of different responders by extracting extensively quantitative features that reflect underlying pathophysiology from medical images (18).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is a research branch in the field of medical imaging (10). Based on the rapid development of machine learning and image processing techniques, radiomic analyses have been successfully applied in the field of oncology (11)(12)(13)(14)(15)(16), including glioma (17). Magnetic resonance imaging (MRI) is a routinely used diagnostic tool for glioma management.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with previous techniques that process medical images as pictures for visual inspection, radiomics introduces a new way to mine the information contained in medical images, and thus, radiomics offers an unprecedented opportunity for clinically assisted diagnosis. 17 Radiomics analysis has been successfully applied to produce imaging biomarkers for neuropsychiatric diseases such as Alzheimer disease, 18 human immunodeficiency virus-related neurodegeneration, 19 and bipolar disorder. Therefore, such studies have demonstrated the potential of radiomics in predicting hippocampal sclerosis.…”
Section: Introductionmentioning
confidence: 99%